Pemanfaatan Media Pembelajaran Berbasis Google Site untuk Meningkatkan Hasil Belajar Peserta didik pada Pembelajaran Bahasa Indonesia di Kelas V SDN 3 Mataram - Nurlaili, Nurlaili; Arjudin; Wardani, Fitria Kusuma (Mataram University, 2025)
This study aims to determine the utilization of Google Site–based learning media to improve students’ learning outcomes in Indonesian language learning. The research employed a Classroom Action Research (CAR) design, with the subjects being 30 fifth-grade students of SDN 3 Mataram. The instruments used included observation sheets and learning achievement tests. Based on the evaluation results in the pre-cycle stage, 26 students (86%) did not achieve mastery, while only 4 students met the passing criteria. In Cycle I, there was an improvement, with 21 students (70%) achieving mastery. In Cycle II, the results increased again, with 26 students (86%) reaching the mastery level. From these findings, it can be concluded that students’ learning outcomes improved significantly. Based on the learning achievement indicator, where at least 85% of students achieved a score of ≥70, it can be stated that the use of Google Site–based learning media effectively improved students’ learning outcomes in Indonesian language learning.